Influencing factors and mechanisms of farmers’ participation in promoting the effect of rural environmental governance—a qualitative comparative analysis based on Chinese cases - Fu, Cheng; Li, Tianfeng; Cao, Lei; Zhou, Fujun (Frontiers in Environmental Science, 2025)
Introduction:Farmers’ participation is the key to promoting the good governance of the rural environment, but the discussion on the effectiveness of farmers’ participation in rural environmental governance is still weak.Methods:A “dynamic-process-guarantee” analytical framework was constructed, and a crisp-set qualitative comparative analysis method was used to explore the linkage effect of various factors such as participation ability, interest correlation, participation channel, supervision & punishment, demand response, and information disclosure, and the path and mechanism of farmers’ participation in improving the effect of rural environmental governance was analyzed.Results:The findings indicate that farmers’ participation in improving the effect of rural environmental governance is the result of multi-factor coupling, and a single factor does not constitute the necessary condition for farmers’ participation in promoting good environmental governance. Participation channel is sufficient conditions for farmers to participate in improving the effect of rural environmental governance. There are five paths and three mechanisms for forming good rural environmental governance effects. Lack of participation ability is a necessary condition for the poor effect of rural environmental governance, and limited participation channels constitute a sufficient condition.Discussion:From the perspective of configuration, the research systematically explains the combination of factors and multiple paths that affect the effect of farmers’ participation in rural environmental governance, which promotes the research of rural environmental governance from a single perspective to an overall multi-dimensional perspective to a certain extent.